(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Psycholinguistics is the discipline that investigates and describes the psychological processes that make it possible for humans to master and use language. Psycholinguists conduct research on speech development and language development and how individuals of all ages comprehend and produce language. For descriptions of language, the field relies on the findings of linguistics, which is the discipline that describes the structure of language. Although the acquisition, comprehension, and production of language have been at the core of psycholinguistic research, the field has expanded considerably since its inception: The neurology of language functioning is of current interest to psycholinguists, particularly to those studying gender differences, aphasia, language after congenital or acquired injury to the immature brain, and developmental disorders of language (dysphasia). Some psycholinguists have also extended their interests to experiments in nonhuman language learning (e.g., gorillas and chimpanzees) to discover if language as we know it is a uniquely human phenomenon.